1985
DOI: 10.1056/nejm198506203122504
|View full text |Cite
|
Sign up to set email alerts
|

The Will Rogers Phenomenon

Abstract: We found that a cohort of patients with lung cancer first treated in 1977 had higher six-month survival rates for the total group and for subgroups in each of the three main TNM stages (tumor, nodes, and metastases) than a cohort treated between 1953 and 1964 at the same institutions. The more recent cohort, however, had undergone many new diagnostic imaging procedures. According to the "old" diagnostic data for both cohorts, the recent cohort had a prognostically favorable "zero-time shift." In addition, by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
226
2
4

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,385 publications
(236 citation statements)
references
References 14 publications
4
226
2
4
Order By: Relevance
“…17,113 A systematic review of six studies, 114 including 465 patients, found an adenoma miss rate of up to 7% for adenomas of ≥ 10 mm, 18% for adenomas of 6-9 mm and 35% for small (≤ 5 mm) adenomas, with an overall miss rate of one in five polyps; flat and sessile serrated lesions were especially likely to be missed. 115,116 The potential for lesions missed at baseline to develop into post-colonoscopy CRCs, 117,118 and the possibility that missed baseline lesions may cause underestimation of risk and improper surveillance recommendations -the Will Rogers phenomenon 119 should be taken into account when considering how soon to perform surveillance after baseline. For this reason, if a patient is deemed to be at sufficient risk to warrant surveillance, the first surveillance should not be delayed.…”
Section: Missed and Incompletely Resected Lesionsmentioning
confidence: 99%
“…17,113 A systematic review of six studies, 114 including 465 patients, found an adenoma miss rate of up to 7% for adenomas of ≥ 10 mm, 18% for adenomas of 6-9 mm and 35% for small (≤ 5 mm) adenomas, with an overall miss rate of one in five polyps; flat and sessile serrated lesions were especially likely to be missed. 115,116 The potential for lesions missed at baseline to develop into post-colonoscopy CRCs, 117,118 and the possibility that missed baseline lesions may cause underestimation of risk and improper surveillance recommendations -the Will Rogers phenomenon 119 should be taken into account when considering how soon to perform surveillance after baseline. For this reason, if a patient is deemed to be at sufficient risk to warrant surveillance, the first surveillance should not be delayed.…”
Section: Missed and Incompletely Resected Lesionsmentioning
confidence: 99%
“…An intensified preoperative staging program revealing distant metastases at the time of presentation can change the classification of a larger proportion of these patients into disseminated disease. This change will also tend to improve survival of the group of patients with metastatic disease as another example of stage migration [29, 30]. This interpretation is supported by the fact that the frequency of patients in the best prognostic groups has increased, and the improved survival of these patients (fig.…”
Section: Discussionmentioning
confidence: 97%
“…The median survival of patients with limited disease (located in pelvic region only) improved from 6.5 to 7.9 months and for patients with liver metastases from 1.9 to 3.9 months in the two periods, respectively. It is likely that detection of liver metastases has been refined due to evaluation with CT scan and that this has introduced stage migration (lead time bias) with improvement of survival in both groups [29, 30]. Careful staging is important because localization of metastases, especially the presence of liver metastases, is an important prognostic factor and because treatment response may depend on this [2, 6, 10].…”
Section: Discussionmentioning
confidence: 99%
“…The HR remained even more reduced after adjustment for the stage. Stage migration 16) could have existed; however, improvement of not only stage-specific survival but also over-all survival may suggest the effectiveness of treatment. 17) Active treatment for metastasis detected by CT or echo might partially explain the increased survival among the patients with distant metastasis.…”
Section: Discussionmentioning
confidence: 99%